Peran BUMDes Dalam Menjadikan Suatu Desa Menjadi Desa Mandiri di Kabupaten Musi Rawas (Sumatera Selatan) - Dyah Hapsari Eko Nugraheni; Andy Alfatih; Diana Dewi Sartika; Randi Randi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Nugraheni DHE, Alfatih A, Sartika DD, Randi R. 2021. The role of BUMDes in turning a village into an independent village in Musi Rawas (South Sumatra Province). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 269-278. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Musi Rawas Regency, based on data from the P3MD Secretariat (Village Community Empowerment Development Program) as of September 2019 there are approximately 183 BUMDes business units. This research aims to obtain the results of evaluation of the successes and failures in the establishment of BUMDes, in order to obtain alternative models for the implementation of the next BUMDes establishment, in line with the research roadmap that has been compiled. Data collection techniques are carried out by means of the dissemination of questionnaires, interviews, observations and documentation with data analysis used, namely descriptive and explanatory statistical techniques. The establishment of BUMDes is considered important because it has a role as a bridge to create the welfare of the village community through an independent village making the village more financially empowered. This means that BUMDes has an important and beneficial role for the welfare of villagers. The issue of the successful establishment of BUMDes in some villages became booming and a warm discourse in other villages, which also wanted to establish BUMDes, as well as BUMDes in some villages that have not succeeded. Therefore, this study can be an input for other villages that do not have BUMDes, including villages that already have BUMDes but have not developed properly.